Method for testing contents of primary and secondary elements in perovskite type ceramic powder
The main and secondary elements contents in the perovskite-type ceramic powder for solid oxide fuel cells were detected by X-ray fluorescence spectrometry, which solved the problems of cumbersome detection steps, long periods and low efficiency in the prior art, and achieved a fast and accurate detection effect.
Patent Information
- Application Number
- CN202411901917.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art shows that when detecting the main and secondary elements contents in perovskite-type ceramic powders for solid oxide fuel cells, the steps are complicated, the detection period is long, the efficiency is low, and the cost is high.
X-ray fluorescence spectroscopy (XRF method) is used in combination with specific sample preparation and measurement steps, including stirring, pre-oxidation, melting and cooling of the sample with mixed flux to form glass sheets, and then the content of each element is determined using an X-ray fluorescence spectrometer.
It realizes rapid and accurate detection of the main and secondary elements content in perovskite ceramic powder, shortens the sample test cycle, from 3-4 days to 0.5 days, reduces the testing cost and improves the detection efficiency.
Smart Images

Figure CN119666902A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of material testing, and in particular to a method for testing the contents of major and minor elements in perovskite-type ceramic powder. Background Art
[0002] Fuel cells can directly convert chemical energy into electrical energy, avoiding the loss of mechanical energy conversion, and the energy conversion efficiency is greater than 50%. Solid oxide fuel cells (SOFCs) are called the third generation of fuel cells. Because of their green and environmentally friendly, easy modular assembly, wide range of fuel selection, and no need for precious metal catalysts, they are considered to be the most promising energy replacement technology in the 21st century and have become a hot research topic in the current energy field. Solid oxide fuel cells are mainly composed of three parts: anode, cathode and electrolyte. The cathode acts as a place to transfer electrons, diffuse oxygen, and provide catalytic oxygen reduction reactions, which has a great influence on battery performance. The cathode materials used in SOFC mainly include metal oxides such as manganese-based oxides, such as lanthanum strontium manganese (LSM), cobalt-based oxides, such as lanthanum strontium cobalt (LSC), and cobalt-iron-based oxides, such as lanthanum strontium cobalt iron (LSCF). The chemical composition of the cathode material is very important for the electrochemical performance and stability of SOFC.
[0003] Combined with the literature on solid oxide fuel cell cathode materials and the relevant products of different manufacturers, the types of elements to be tested, the test range and marking points are confirmed, see Figure 4 shown.
[0004] The current industry Figure 4The analysis of each component was carried out by wet chemical method. The iron content in ceramic powder was determined by titanium trichloride-potassium dichromate titration method in reference to GB / T8654.1-2007 "Metallic manganese, manganese silicon alloy, ferromanganese and ferromanganese nitride-Determination of iron content-o-phenanthroline spectrophotometric method and titanium trichloride-potassium dichromate titration method"; the strontium and lanthanum contents in ceramic powder were determined by reference to "YS / T 1339-2019 Chemical analysis method of doped nickel, cobalt and manganese three-element composite hydroxide-Determination of aluminum, magnesium, titanium, strontium, zirconium, lanthanum and yttrium content-Inductively coupled plasma atomic emission spectrometry"; the nickel content in ceramic powder was determined by reference to "YS / T 928.2-2013 Chemical analysis method of nickel, cobalt and manganese three-element hydroxide-Part 2: Determination of nickel content-Dimethylglyoxime gravimetric method"; the nickel content in ceramic powder was determined by reference to "YS / T The nickel, cobalt and manganese contents in ceramic powders were determined by referring to "928.3-2013 Chemical analysis methods for nickel, cobalt and manganese hydroxides - Part 3: Determination of nickel, cobalt and manganese content - Inductively coupled plasma atomic emission spectrometry"; the barium content in ceramic powders was determined by referring to "YB / T 178.2-2012 Determination of barium content in silicon-aluminum alloys and silicon-barium-aluminum alloys - Barium sulfate gravimetric method"; the barium and cerium contents in ceramic powders were determined by "YB / T 4231-2010 Determination of aluminum, barium, iron, calcium, manganese, copper, chromium, nickel and phosphorus contents in silicon-barium-aluminum, silicon-calcium-barium and silicon-calcium-barium-aluminum alloys - Inductively coupled plasma atomic emission spectrometry".
[0005] The determination of iron adopts titration method, nickel and barium adopt weight method or ICP method, and cobalt, manganese, lanthanum, strontium and cerium adopt ICP method. The wet chemical method is cumbersome to dissolve samples, the test process is long, and the technical level of personnel is high. In addition, the amount of acid used in the wet chemical method is large, which is not environmentally friendly. In addition, these methods require individual elements to be tested, making it difficult to detect the main, secondary and trace components at the same time. To complete the analysis of all element contents, the test cycle of a sample takes 3-4 days.
[0006] Therefore, it is more important to quickly and accurately detect the quality of perovskite ceramic powders for solid oxide fuel cells and the content of major and minor elements in ceramic powders. How to improve the detection efficiency of the major and minor element content of perovskite ceramic powders for solid oxide fuel cells has become the main content of this research topic. Summary of the invention
[0007] The purpose of the present invention is to provide a testing method for the content of major and minor elements in perovskite ceramic powders, so as to solve the problems of the existing testing standards "YS / T 1339-2019", "YS / T 928.2-2013", "YB / T 178.2-2012", etc., such as complicated testing steps, many factors affecting the accuracy of the test results (such as the proficiency of the test personnel), long testing cycle, low testing efficiency and high testing cost.
[0008] To achieve the above object, the present invention provides the following technical solution: a method for testing the content of major and minor elements in perovskite ceramic powder, comprising the following steps: Step 1, weigh the sample and mixed flux into a platinum crucible, stir evenly, add lithium nitrate solution and drop lithium bromide solution; Step 2, pre-oxidizing the mixed material in step 1 in a high temperature environment; Step 3, continue to heat up and melt and shake, then pour into a platinum mold to form a uniform glass sheet, remove the glass sheet from the mold after cooling, and measure under the selected measurement conditions; Step 4, weighing the mixed flux and placing it in a platinum crucible, weighing the oxide containing the element to be measured in proportion, adding lithium nitrate solution and lithium bromide solution, and preparing a standard sheet according to steps 2 and 3; Step 5, optimizing the test conditions, and using an X-ray fluorescence spectrometer to measure the standard film and draw a standard curve; Step 6, testing the glass sheet, and calculating the contents of major and minor elements in the perovskite ceramic powder for solid oxide fuel cells according to the working curve method.
[0009] Step 7, based on the measured X-ray fluorescence intensity of the characteristic spectrum of each element in the glass sheet, calculate the content of each element according to the calibration equation: Ci=Cm··················(1) Ci is the content of the measured element; Cm is the machine-readable value of the measured element.
[0010] Preferably, in step 1, the sample mass is 0.900 g, the mixed flux mass is 9.000 g, the oxidant lithium nitrate solution is 1.0 ml, and the release agent solution is 3 drops.
[0011] Preferably, in step 2, the mixed material is pre-oxidized at 700° C. for 2 min.
[0012] Preferably, in step 3, the melting procedure is melting at 1200° C. for 12 min, shaking for 8 min, and the sample is automatically introduced into a platinum mold and cooled into a uniform glass sheet.
[0013] Preferably, in step 4, the composition and content of the standard sample are designed according to the content of the component to be measured, the content of each oxide is weighed, and the standard piece is manually configured.
[0014] Preferably, the detection limit of each element is 0.020%-0.082%, and the relative standard deviation of the method is 0.61%-2.73%.
[0015] Preferably, the mixed flux is m(Li2B4O7):m(LiBO2)=33:67.
[0016] Preferably, in step 5, the test conditions are optimized, including the selection of current, voltage, and spectroscopic crystal: if there is interference from the matrix spectrum line, a crystal with a smaller 2d value is selected; the voltage setting value is greater than the excitation potential of the element to be measured, and is 0.7 to 0.9 times the full power; Filter selection: After testing the signal-to-background ratio of each element, select the filter without filter, Al200, Al750 and Brass400, and then select the high signal-to-background ratio; Matrix effect and spectral line overlap correction: The matrix correction model is used to correct the absorption and enhancement effects of other elements, and the Sherman relationship is used to calculate the matrix correction coefficient M, which is expressed as follows:
[0017] Where C i is the content of the element to be measured, D i is the intercept; E i is the slope of the curve; R i is the spectral line intensity; M i Matrix correction factor. Spectral line overlap correction can be added through the Sherman relationship to control the parameters of spectral line overlap Expanded.
[0018] The matrix effect was reduced by melting sample preparation by appropriately increasing the flux dilution ratio. The calibration curve was drawn using standard samples prepared with high-purity metal compounds. By optimizing the sample preparation conditions and analyzing the interference of spectral line overlap, the contents of eight major and minor elements in the cathode material for SOFC were quickly and accurately determined by X-ray fluorescence spectrometry.
[0019] Compared with the prior art, the present invention has the following beneficial effects: the present invention can simultaneously determine light and heavy elements by using the XRF method, has a fast analysis speed, a wide range of applications, a low analysis cost, is environmentally friendly, and is very suitable for rapid detection of batch samples.
[0020] The sample testing cycle was shortened from 3 to 4 days to 0.5 days, which greatly improved the detection rate and reduced the testing cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is the overall flow chart of the present invention; Figure 2 For comparison between the present invention and other testing methods; Figure 3 It is the spectral line overlapping interference diagram of the present invention; Figure 4 It is a table of the types of elements to be tested, test ranges and marking points of the present invention. DETAILED DESCRIPTION
[0022] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] Unless otherwise specified, the equipment and reagents used in the embodiments and test examples can be obtained from commercial sources, and are listed in detail as follows: Cerium dioxide (≥99.95%), baked at 105℃ for 2 h; manganese dioxide (≥99.95%), baked at 105℃ for 2 h; strontium nitrate (≥99.97%), baked at 105℃ for 2 h; barium oxide (≥99.95%, Sr <500ppm), baked at 105℃ for 2 h; cobalt trioxide (≥99.5%), baked at 105℃ for 2 h; ferric oxide (≥99.9%), baked at 105℃ for 2 h; lanthanum nitrate hexahydrate (99.99%), nano nickel powder (99.9%, 100nm-200nm); lithium nitrate solution (220g / L); lithium bromide solution (100g / L); XRF special mixed flux [m(Li2B4O7):m(LiBO2)=33:67], high-grade purity.
[0024] Requirements for the ratio of sample volume to flux: moderate ratio to reduce the measurement error of low-content elements; ensure that the reducing substances in the sample are fully oxidized to protect the platinum crucible from corrosion; the molten material has good fluidity and can be spread flat on the bottom of the mold.
[0025] Requirements for the mixed flux ratio: good fluidity, uniform sample body, and no small bubbles at the edge of the sample.
[0026] Requirements for melting temperature and melting time: The melt has good fluidity and is easy to pour into the mold without any insoluble matter; it is completely melted and easy to demold; the glass sheet has good mechanical strength, is stable, and is not easy to break.
[0027] Choice of oxidant: The prepared sample pieces were uniform and complete, and no corrosion was found in the crucible.
[0028] Selection of current, voltage and spectroscopic crystal: In case of interference from matrix spectral lines, select a crystal with a smaller 2d value; the voltage setting value should be greater than the excitation potential of the element to be measured, preferably 0.7~0.9 times of full power.
[0029] Filter selection: No filter, Al200, Al750 and Brass400 filters were selected to test the signal-to-background ratio of each element, and the highest signal-to-background ratio was selected as the best.
[0030] Matrix effect and spectral line overlap correction: The matrix correction model is used to correct the absorption and enhancement effects of other elements, and the Sherman relationship is used to calculate the matrix correction coefficient M, which is expressed as follows:
[0031] Where C i is the content of the element to be measured, D i is the intercept; E i is the slope of the curve; R i is the spectral line intensity; M i Matrix correction factor. Spectral line overlap correction can be added through the Sherman relationship to control the parameters of spectral line overlap Expanded.
[0032] In the present invention, accuracy refers to the degree of conformity between the measured value and the true value, and is usually characterized by the accuracy of the test data. Accuracy reflects the comprehensive index of the systematic error or random error in the measurement method or system, which determines the reliability of the analysis result. The evaluation indicators of accuracy include method comparison, standard sample comparison and spiked recovery rate.
[0033] Method comparison in this invention refers to comparing the test method (method to be evaluated) with the comparison method (reference method) to determine the difference between the results and understand the bias of the test results of the evaluation method to be tested. Generally, the t test is used to determine the difference between the two results. If t is less than the critical value t under the significance level α (α=0.05) and the degree of freedom (n1+n2-2), the difference between the two results is not significant. α (n1+n2-2), there is no significant difference between the two results; n1 is the number of tests for the first method; n2 is the number of tests for the second method.
[0034] In the present invention, precision reflects the magnitude of random errors in the measurement method or system. The smaller the random error of the test result, the higher the test precision. Precision is usually expressed in terms of range, standard deviation and relative standard deviation. The precision is mainly examined in three forms: parallelism, repeatability and reproducibility.
[0035] The detection limit in the present invention refers to the minimum concentration or minimum amount of the substance to be tested that can be qualitatively detected from the sample by a specific analytical method within a given confidence level. The detection limit determination and calculation method in this part is shown in formula (3):
[0036] Where: L D is the detection limit, ug / g; S is the measurement sensitivity, cps / ppm; R b is the background intensity, cps; T b is the measurement time, s; n is a constant with a value of 2, corresponding to a significance of 2 and a confidence level of 95%.
[0037] The lower limit of determination in the present invention refers to the minimum concentration of the analyte that can be accurately and quantitatively determined by a specific method under the condition that the measurement error can meet specific requirements.
[0038] The correlation coefficient R of the fitting curve in the present invention is 2 , is a statistical indicator used to measure the correlation between two variables; R 2 The closer to 1, the better the linearity. For the concentration range of the standard curve in the XRF method for measuring the content of major and minor elements in perovskite ceramic powders for solid oxide fuel cells, at least 5 points were selected within the determination limit, and the linear correlation coefficient R 2 ≥0.999.
[0039] Example 1: Selection of sample amount and flux ratio Step 1: According to step 1 of the invention, weigh 3 portions of sample 1#, melt the sample in a platinum crucible with a mixed flux to sample mass ratio of 5:1, 10:1, and 20:1, respectively, stir evenly, and add 1 mL of lithium nitrate solution and 3 drops of lithium bromide solution.
[0040] Step 2: Perform a sample size and flux ratio selection test according to the sample preparation steps 2~3 and measurement step 6.
[0041] Step 3: The test shows that when the mass ratio of the melt to the sample is 5:1, the fluidity of the melt is poor, and a transparent sample flake cannot be formed. At the same time, the reproducibility of sample preparation is poor. When the mass ratio is 20:1, the fluidity of the melt is very good, and the elements with low content cannot meet the detection requirements, and the analysis error is large. The use of a mass ratio of 10:1 can not only prepare high-quality flakes and reduce the measurement error of low-content elements, but also ensure that the reducing substances in the sample are fully oxidized to protect the platinum crucible from corrosion.
[0042] Example 2: Selection of mixed flux ratio Step 1: According to step 1 of the invention, 3 portions of samples 1# and 2# were weighed, and mixed fluxes (lithium tetraborate: lithium metaborate) with mass ratios of 67:33, 50:50, and 12:22 were selected for melting and sample preparation.
[0043] Step 2: Perform the flux selection test according to the sample preparation steps 2~3 and measurement step 6.
[0044] Step 3: Study the effects of three different fluxes on the sample and the results. The results are shown in Table 2. The test results show that the flux lithium tetraborate-lithium metaborate mixed flux (67:33) has the best melting effect. Refer to the table below:
[0045] Example 3: Selection of melting temperature and melting time: Step 1: According to experience, the melting temperature is generally selected between 1000℃ and 1200℃, which is 200℃ higher than the melting point of the flux. The melting point of lithium borate is 920℃, and the melting point of lithium metaborate is 845℃.
[0046] Step 2: According to step 1 of the invention, weigh 5 portions of 2# sample Step 3: Perform the test according to step 2 of preparing the sample sheet, and change the melting temperature to 1000°C, 1050°C, 1100°C, 1150°C, and 1200°C in sequence to perform temperature melting tests to determine the optimal melting temperature, and perform the test on the machine according to step 6 of the invention.
[0047] Step 4: The results are shown in Table 3. Table 3 shows that at 1100 ℃, 1150 ℃, and 1200 ℃, the melt has good fluidity, the sample pieces are uniform, and there is no infusible material. However, considering that most oxides have high melting points, 1200 ℃ is selected as the melting temperature. The melting temperature test is shown in the following table
[0048] Step 5: Melting time is related to the quality of the melt. Long time will cause the sample to stick and be difficult to pour out; short time will lead to uneven mixing of the sample, incomplete melting and even crystallization, resulting in sample fragmentation and inability to analyze.
[0049] Step 6: Set the melting time on the automatic melting furnace to 8 min, 12 min, and 18 min for testing.
[0050] Step 7: The results show that: when the melting time is 8 minutes, the melting is not complete, and tiny particles remain in the glass melt, which leads to sample fragmentation; when the melting time is 18 minutes, the melting is complete, but sometimes the glass melt adheres to the platinum crucible; and when the melting time is 12 minutes, the melting is complete and easy to demold. The glass piece has good mechanical strength, is stable, and is not easy to break and absorb water, which can fully meet the requirements of X-ray fluorescence spectrometry analysis. Therefore, the melting time of 12 minutes was selected for the experiment.
[0051] Example 4: Selection of oxidant and dosage.
[0052] Step 1: Add ammonium nitrate, sodium or lithium in a concentration of several percent to the flux to oxidize a small amount of organic matter or partially oxidized elements and reduce corrosion to the crucible.
[0053] Step 2: There is no significant difference when adding the oxidant ammonium nitrate or lithium nitrate during melting. Ammonium nitrate and lithium nitrate are more suitable, but ammonium nitrate is more difficult to purchase.
[0054] Step 3: In this test, lithium nitrate is selected as the oxidant, which is first prepared into a 220 g / L aqueous solution, and the solution is prepared so that it can fully contact with the sample to facilitate the oxidation of the sample.
[0055] Step 4: In this test, 3 portions of 1# sample were weighed and tested according to the preparation and determination steps of the sample sheet. 0.5ml, 1ml, and 2ml of lithium nitrate solution were added respectively to carry out the test, and the optimal amount of lithium nitrate solution was determined through the test.
[0056] Step 5: When the temperature of lithium nitrate exceeds 600℃, it decomposes into oxidizing substances, nitrogen dioxide and oxygen. The pre-oxidation temperature is selected to be 700℃ for the test. The test results are shown in Table 3, indicating that adding 1ml of oxidant can not only obtain a uniform and complete test piece, but also prevent the crucible from being corroded. The selection experiment of oxidant and dosage is shown in the following table:
[0057] Example 6: Selection of Spectroscopic Crystal Step 1: Spectral splitting crystals can improve resolution and detection efficiency; according to the Bragg formula sinθ=nλ / 2d (where λ is the wavelength of the X-ray, n is the diffraction order, d is the crystal plane spacing, and θ is the angle between the incident X-ray and the corresponding crystal plane), if the angle between the two spectral lines is increased, that is, the sinθ value increases, then the 2d value needs to be reduced, that is, a crystal with a smaller 2d value should be selected for spectrometry.
[0058] Step 2: The Sr Lα line is less affected by matrix elements, so PE (002) crystal is selected. Other elements such as Ba, Fe, Mn, and Ni are all interfered by matrix spectral lines, so LiF200 and LiF220 crystals with smaller 2d values are selected.
[0059] Example 7: Selection of filter Step 1: The purpose of the filter is to eliminate or reduce the interference from the X-ray spectrum, especially the X-ray spectrum of the target material, on the element to be measured, which can improve the peak-to-background ratio and increase the sensitivity of the analysis.
[0060] Step 2: In this experiment, no filter, Al200, Al750 and Brass400 filters were selected to test the signal-to-background ratio of each element.
[0061] Step 3: The signal intensity and signal-to-background ratio under each filter condition are shown in Table 5. It can be seen from Table 5 that when the brass filter Brass400 is used, the signal intensity is low and the signal-to-background ratio is small due to the large absorption of the filter on the signal intensity; except for Sr, the signal intensity and signal-to-background ratio of the elements to be measured using the Al200 filter are better than those of the Al750 filter, and the signal-to-background ratios of the two filters are greater than those of the brass filter Brass400; as the thickness decreases, the signal intensity and signal-to-background ratio of the elements to be measured gradually increase.
[0062] Step 4: When the filter is not used, the signal-to-background ratio of the measured result becomes worse. This is because the background signal is too large when the filter is not used, which affects the signal-to-background ratio. After the filter is used for Sr, most of the SrLα signal is filtered out, and the intensity is too small to be measured, so it is not listed in Table 5. Therefore, it is recommended that Sr not use a filter. The types of aluminum sheets are as follows:
[0063] Step 5: By optimizing the selection of instrument parameters, while ensuring the sensitivity of the measurement, the final optimized analysis conditions of each element are shown in the following table:
[0064] Example 8: Matrix Effect and Spectral Line Overlap Correction Step 1: Matrix effect refers to the influence of the changes in the chemical composition and physical-chemical state of the sample on the characteristic X-ray intensity of the element to be analyzed. The matrix effect is divided into inter-element absorption effect and enhancement effect. On the one hand, the melting method can eliminate the influence of mineral effect and particle size effect on the results. On the other hand, the elements to be tested are the major and minor elements of the sample, and the content is relatively high. At the same time, the mass ratio of the sample to the flux in this method is 1:10, which reduces the influence of the matrix effect on the test to a certain extent.
[0065] Step 2: Use the matrix correction model to correct the absorption and enhancement effects of other elements, and use the Sherman relationship (Formula 2) to calculate the matrix correction coefficient M; Step 3: The method to solve the spectral line overlap is to subtract the influence of the interference spectral line from the analysis spectral line. The correction model adds the parameter f to control the spectral line overlap through the Sherman relationship (Equation 2) ij It is expanded to get formula (4), where C j is the content of interfering elements. The element to be measured selects a spectrum line with less spectral interference and intensity that meets the requirements, and calculates the spectral line overlap coefficient f of the element to be measured ij Select the spectrum line with less interference and intensity that meets the requirements, and calculate the spectrum line overlap coefficient f of other elements to be measured. ij See Table 7.
[0066]
[0067] The spectral line correction coefficients of the elements to be measured are as follows:
[0068] Step 4: After correcting the spectral interference using the correction formula, the calibration curve parameters of the cathode material metal oxide are shown in the following table:
[0069] Example 9: Method Detection Limit Step 1: In actual sample testing, the detection limit is often related to the sample matrix. Since different samples have different elemental compositions and contents, as well as different scattering backgrounds, the calculated detection limit may differ from the actual one.
[0070] Step 2: Use formula (3) to calculate the detection limit LD. It can be seen from the formula that extending the measurement time can reduce the detection limit.
[0071] Step 3: Calculate the detection limit according to formula (3). The detection limits of the eight elements are in the range of 0.013% to 0.082%. The detection limits are shown in the table below. The detection limits of each element are all below 0.1%, which can meet the test requirements for the composition of SOFC cathode materials.
[0072]
[0073] Example 10: Method Precision
[0074] Example 11: Method Accuracy By comparing the determination results of this method with those of the wet chemical method, the consistency between the test results of the two methods was examined by the t-test method; both methods were tested twice in parallel, and if t was less than the critical value t at the significance level α (α=0.05), the results were consistent. 0.05 (2) (t 0.05 (2) = 4.303), there is no significant difference between the two results. As can be seen from the table below, the results of this method are in good agreement with those of the wet method, and the accuracy meets the analytical requirements.
[0075]
[0076] a : ICP-OES method; b : Gravimetric method By using artificial mixed samples as calibration samples, the problem of missing standard substances was solved; and the interference of matrix effect and spectral line overlap effect on the determination of SOFC cathode material components was effectively corrected; the detection limit of this method for the determination of each element was 0.020%~0.082%, and the relative standard deviation (RSD, n=6) of the method was 0.61%~2.73%, which was consistent with the results of the laboratory dissolution method.
[0077] This method can quickly and accurately determine the contents of 8 major and minor elements in SOFC cathode materials, and can meet the laboratory's daily testing requirements for cathode material components. It is a fast, simple and green analysis method. It overcomes the shortcomings of the wet chemical method, which is cumbersome, long and costly. The test cycle is shortened from 3 to 4 days to 0.5 days, significantly improving the detection rate. Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for testing the content of primary and secondary elements in perovskite ceramic powder, characterized in that: The steps include: Step 1, weigh the sample and mixed flux into a platinum crucible, stir evenly, add lithium nitrate solution and drop lithium bromide solution; Step 2, pre-oxidizing the mixed material in step 1 in a high temperature environment; Step 3, continue to heat up and melt and shake, then pour into a platinum mold to form a uniform glass sheet, remove the glass sheet from the mold after cooling, and measure under the selected measurement conditions; Step 4, weighing the mixed flux and placing it in a platinum crucible, weighing the oxide containing the element to be measured in proportion, adding lithium nitrate solution and lithium bromide solution, and preparing a standard sheet according to steps 2 and 3; Step 5, optimizing the test conditions, and using an X-ray fluorescence spectrometer to measure the standard film and draw a standard curve; Step 6, testing the glass sheet and calculating the contents of the main and secondary elements in the perovskite ceramic powder according to the working curve method; Step 7, based on the measured X-ray fluorescence intensity of the characteristic spectrum of each element in the glass sheet, calculate the content of each element according to the calibration equation: Ci=Cm··················(1) Ci is the content of the measured element; Cm is the machine-readable value of the measured element.
2. The method for testing the content of major and minor elements in a perovskite ceramic powder according to claim 1, characterized in that: In step 1, the sample mass is 0.900 g, the mixed flux mass is 9.000 g, the oxidant lithium nitrate solution is 1.0 ml, and the release agent solution is 3 drops.
3. The method for testing the content of major and minor elements in a perovskite ceramic powder according to claim 1, characterized in that: In step 2, the mixed material was pre-oxidized at 700 °C for 2 min.
4. The method for testing the content of major and minor elements in a perovskite ceramic powder according to claim 1, characterized in that: In step 3, the melting procedure is 1200 °C for 12 min, rocking for 8 min, and the sample is automatically introduced into a platinum mold and cooled into a uniform glass sheet.
5. The method for testing the content of major and minor elements in a perovskite ceramic powder according to claim 1, characterized in that: In step 4, the composition and content of the standard sample are designed according to the content of the component to be measured, the content of each oxide is weighed, and the standard piece is manually configured.
6. The method for testing the content of major and minor elements in a perovskite ceramic powder according to claim 1, characterized in that: The detection limits of each element were 0.020%-0.082%, and the relative standard deviation was 0.61%-2.73%.
7. The method for testing the content of major and minor elements in a perovskite ceramic powder according to claim 1, characterized in that: The mixed flux is m(Li2B4O7):m(LiBO2)=33:
67.
8. The method for testing the content of major and minor elements in a perovskite ceramic powder according to claim 1, characterized in that: In step 5, the test conditions are optimized, including the selection of current, voltage, and spectrometer wafers: in case of interference from the matrix spectrum, a crystal with a smaller 2d value is selected; the voltage setting value is greater than the excitation potential of the element to be tested, and is 0.7 to 0.9 times the full power; Filter selection: After testing the signal-to-background ratio of each element, select the filter without filter, Al200, Al750 and Brass400, and then select the high signal-to-background ratio; Matrix effect and spectral line overlap correction: The matrix correction model is used to correct the absorption and enhancement effects of other elements, and the Sherman relationship is used to calculate the matrix correction coefficient M, which is expressed as follows: Where C i is the content of the element to be measured, D i is the intercept; E i is the slope of the curve; R i is the spectral line intensity; M i Matrix correction factor. Spectral line overlap correction can be added through the Sherman relationship to control the parameters of spectral line overlap Expanded.
Citation Information
Patent Citations
Method for determining content of calcium fluoride in fluorite with X-ray fluorescence spectrum melting method
CN106290438A
Quantative analysys method for dielectric substance of multi-layer ceramic capacitor
KR1020130075488A